Unraveling the Genetic Landscape of Psoriasis: A Genome-Wide Association Study in Egypt - Abd El Nasser; Nazeera Hamid (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Psoriasis is a chronic inflammatory skin disease with a complex genetic basis. While Genome-Wide Association Studies (GWAS) have identified numerous susceptibility loci in European populations, the genetic landscape of psoriasis in Egyptians remains largely unexplored. Methods: The study conducted a GWAS in a cohort of 1,200 Egyptian individuals (600 cases and 600 controls) using the Illumina Infinium Global Screening Array-24 v3.0 BeadChip. After stringent quality control, association analyses were performed using logistic regression, adjusting for age, sex, and principal components. Replication of top signals was attempted in an independent cohort of 500 Egyptian individuals (250 cases and 250 controls). Functional annotation and pathway enrichment analyses were performed to gain insights into the biological relevance of associated loci. Results: We identified novel genome-wide significant associations in the HLA region (rs10484554: p = 1.2 x 10^-15, OR = 2.3) and near the IL23R gene (rs11209026: p = 3.5 x 10^-9, OR = 1.7). These associations were replicated in the independent cohort. Additionally, we observed suggestive associations near several genes previously implicated in psoriasis, including IL12B, TRAF3IP2, and CARD14. Pathway enrichment analyses highlighted the involvement of immune response, cytokine signaling, and keratinocyte differentiation pathways. Conclusion: This GWAS in Egyptians has revealed novel psoriasis susceptibility loci and replicated previously reported associations, contributing to a better understanding of the genetic architecture of psoriasis in this population. These findings may have implications for the development of personalized treatment strategies.